2012
DOI: 10.1016/j.cell.2012.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Biochemically Distinct Vesicles from the Endoplasmic Reticulum Fuse to Form Peroxisomes

Abstract: As a rule, organelles in eukaryotic cells can derive only from pre-existing organelles. Peroxisomes are unique because they acquire their lipids and membrane proteins from the endoplasmic reticulum (ER), whereas they import their matrix proteins directly from the cytosol. We have discovered that peroxisomes are formed via heterotypic fusion of at least two biochemically distinct preperoxisomal vesicle pools that arise from the ER. These vesicles each carry half a peroxisomal translocon complex. Their fusion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
6
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(208 citation statements)
references
References 54 publications
(58 reference statements)
13
185
6
4
Order By: Relevance
“…Past results show that both vesicular and nonvesicular transport of lipids and proteins from the ER are required for proper peroxisomal formation and maintenance (Raychaudhuri and Prinz 2008;Lam et al 2010;Agrawal et al 2011;van der Zand et al 2012). In vitro ER-peroxisome lipid transfer assays also show nonvesicular transport between the membrane compartments; however, the proteins mediating this process remain to be identified (Raychaudhuri and Prinz 2008).…”
Section: Er and Peroxisomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Past results show that both vesicular and nonvesicular transport of lipids and proteins from the ER are required for proper peroxisomal formation and maintenance (Raychaudhuri and Prinz 2008;Lam et al 2010;Agrawal et al 2011;van der Zand et al 2012). In vitro ER-peroxisome lipid transfer assays also show nonvesicular transport between the membrane compartments; however, the proteins mediating this process remain to be identified (Raychaudhuri and Prinz 2008).…”
Section: Er and Peroxisomesmentioning
confidence: 99%
“…In vitro ER-peroxisome lipid transfer assays also show nonvesicular transport between the membrane compartments; however, the proteins mediating this process remain to be identified (Raychaudhuri and Prinz 2008). Recent live cell image analysis and in vitro cell-free ER budding assays identified a distinct pool of vesicles rich in peroxisomal membrane proteins budding from the ER at peroxisomal ER exit sites, these vesicles then underwent heterotypic fusion with other ER-derived peroxisomal membrane protein vesicles to form a new peroxisome compartment (Agrawal et al 2011;van der Zand et al 2012). The ER-derived peroxisome remains a striking example of the ER's ability to generate an organelle distinct from itself in both morphology and function.…”
Section: Er and Peroxisomesmentioning
confidence: 99%
“…Peroxisomes are generated by two different mechanisms: They can form de novo from the endoplasmic reticulum or by growth and division from pre-existing peroxisomes. The contribution of the two pathways to peroxisome biogenesis is a matter of intensive debate [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…To underscore this notion, a subset of ER resident proteins have emerged as constituents of maturing phagosomes giving rise to a mechanistic basis for antigen cross presentation in innate immunity (Gagnon et al 2002;Houde et al 2003;Cebrian et al 2011;Campbell-Valois et al 2012). The ER also generates peroxisomes (Titorenko et al 1997;Titorenko and Rachubinski 1998;van der Zand et al 2012), and a further specialized subset of ER is found beneath the cell membrane of many cells (English et al 2009). The Golgi apparatus, on the other hand, contributes part of its machinery to lipid droplet biogenesis, revealing a mechanistic link previously thought to be exclusive to that of the ER.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%